Średniowieczne "clausulae" różańcowe i ich teologiczna treść - Lekan, Janusz (Verbum Vitae, 2024)
This theological reflection focuses on one form of Marian devotion, the Rosary. This prayer, which has been known for centuries, has a deep theological meaning: it introduces the mysteries of salvation (doctrine) and is a form of meditative prayer (spirituality). As a prayer, it also needs renewal, as encouraged by Pope Paul VI in his exhortation Marialis cultus. The medieval forms of Clausular Rosary could become a way of renewing this prayer. However, before the historical and theological context of its origin is shown, it is necessary to point out the nature of Marian devotion and its place in Christian piety. After discussing the historical and theological context of how the clausulae were formed and the role of Dominic of Prussia in this process, the actuality of this prayer shall be emphasised by pointing out its theological richness: its biblical and contemplative value. The Clausular Rosary also has ecumenical value, since this form of prayer has strictly biblical roots: it contains the Angelic Salutation described in the Gospel of St. Luke and a reference to the mysteries of salvation accomplished by Jesus Christ. It is also a response to the popularity of meditation in the spirit of Eastern religions.